Odjek mesijanizma Adama Mickiewicza u djelu Ivana Mažuranić / Echo Mickiewiczowskiego mesjanizmu w twórczości Ivana Mažuranicia (tłum. Leszek Małczak) - Rogić Musa, Tea; Małczak, Leszek (Przekłady Literatur Słowiańskich, 2015)
The echo of Adam Mickiewicz’s messianism in the work of Ivan Mažuranić This paper presents Mažuranić’s early translations of Adam Mickiewicz, including the threefold thematic orientation: first we try to shed some light on the origin of six unsigned translation fragments from Mickiewicz’s The Books of the Polish People and of the Polish Pilgrimage, printed in “Danica” in 1837, whose authorship has been attributed differently in literature. Mickiewicz’s work had a significant impact on the Illyrians, and those fragments were the earliest translations of that political work among the South Slavs. The translation consists of a series of prose notes that are a free rewriting of the original, adapted to Croatian circumstances, and very successful as a whole, with an excellent imitation of Mickiewicz’s biblical‑rhetorical rhythm. We will document Mažuranić’s familiarity with Mickiewicz’s work through a possible direct intertextual and literary historic‑poetological relationship between Mickiewicz’s political writings and Mažuranić’s brochure Croats and Hungarians and finally elaborate on the influence of Polish messianism — in its variant found in Mickiewicz’s political writings — on the young Mažuranić in the atmosphere of the Croatian National Revival. Key words: Ivan Mažuranić; Adam Mickiewicz; messianism; The Books of the Polish People and of the Polish Pilgrimage; Croatian National Revival.